MODERN METHODS OF CORONO-RADICULAR RESTORATION OF A LATERAL TOOTH WITH AN ENDODONTIC TREATMENT - Anca-Elena But; Paula Perlea; Alexandru Titus Farcaşiu; Mihaela-Rodica Păuna (Amaltea Medical Publishing House, 2018)
Most of the teeth that require endodontic treatment have been affected by extensive caries. These weakened them, increasing their risk of fracture and making their restoration much more difficult for the dento-maxillary function to restore. Modern dentistry offers various possibilities for restoring endodontically treated teeth. The best option is selected by the clinician according to the clinical case particularities. This article is a summary of the modern methods used for restoring a lateral tooth with an endodontic treatment.